(untitled) (International Journal of Physiotherapy, 2025)
Background: Coronary artery bypass graft (CABG) is the most common treatment for relieving symptoms and reducing early mortality in patients with coronary artery disease. Cardiac rehabilitation (CR) is a standardized physical and functional enhancement program. The referral rate for cardiac rehabilitation post-operatively is very low, and further compliance is a bigger problem. Tele cardiac rehabilitation is beneficial for increasing participation in CR. Therefore, this study will assess the effect of tele CR on patients with CABG. Methods: A randomized controlled trial was conducted in a multispecialty hospital for four years. A total of 48 consecutive CABG patients were included and divided into a telerehabilitation and home exercise group through convenient sampling. Patients of both groups were unaware of group allocation and were assessed for functional independence, hand grip strength, and 6-minute walk test distance at discharge, at 1 month, and at 3 months postdischarge. Results: At 3 months post-discharge, patients in the tele cardiac rehabilitation group showed statistically significant improvement in functional status (p=0.041) and functional capacity (p=0.019). Hand grip strength was not different in both groups (p=0.162) after 3 months of discharge. Conclusion: Tele-cardiac rehabilitation benefits patients with CABG who cannot attend center-based cardiac rehabilitation and want to improve their daily lives.